The management audit as a tool to foster corporate governance: an inquiry in Switzerland. Issue 8 (5th October 2015) - Brender, Nathalie; Yzeiraj, Bledi; Fragniere, Emmanuel
Abstract : Purpose: – This paper aims to investigate management auditing, a thorough examination of an organization and the management in place, through an empirical research to gather data about how management audits are perceived and implemented among Geneva's (Switzerland) business community. The board of directors is in charge of a corporation's overall supervision. The internal auditing function works under the aegis of the board to ensure that the directors will properly execute their responsibilities as defined by corporate governance rules. Management auditing could thus be used to improve corporation performance. However, management audits are not commonly used or referred to as a tool to address corporate governance. Findings enable the authors to both explain why management audits are not commonly used or referred to as a tool to address corporate governance and generate related research hypotheses. Design/methodology/approach: – In this paper, the authors rely on an ethnographic study aimed at exploring perceptions of management audits in service companies from the Geneva region. This study is based on transcripts from 85 semi-directed interviews, conducted over a three-year period, of professionals with managerial and auditing backgrounds. The economic context during these three years was consistently characterized by the Swiss and international financial crises, ensuring that the findings remain comparable over this time period. Findings: – This paper identified three main factors that influence the integration of management audits into corporate practices: the degree of acceptance of the tools and requirements of management audits, the national culture and values embodied in the practice and the degree of corporate governance maturity. This paper presents the findings in the form of hypotheses that can be tested on any adoption of good corporate governance practices – not on management audits alone. Research limitations/implications: – Notwithstanding the limitations due to its nature and extent, this study's main limitation is its lack of validation of the hypotheses. In further research, the authors intend to use a quantitative survey to validate the research hypotheses and make statistical inferences. Originality/value: – This paper contributes to the literature because it is, to the authors' knowledge, the first study to empirically examine the significant link between management audits and corporate governance. The findings could be interesting for an international audience because they indicate possible action points that boards of directors can leverage to carry out management audits. The findings also bridge a gap between the literature on management audits and the expanding role of the internal audit function. This study also examines the way companies – in the Swiss context – understand, perceive and may be ready to apply management audits as a good corporate governance practice.